Improved photodegradation of antibiotics pollutants in wastewaters by advanced oxidation process based on Ni-doped TiO2. (September 2022) - Nguyen, Thanh Luan; Pham, Thi Huong; Viet, Nguyen Minh; Thang, Phan Quang; Rajagopal, Rajakrishnan; Sathya, Rengasamy; Jung, Sung Hoon; Kim, Taeyoung
Abstract: The number of antibiotic compounds in wastewaters has been growing globally due to the covid-19 problem. Using antibiotics to treat the patients would produce larger amounts of these compounds into the environment with negative impacts. Hence, finding out the method for the elimination of toxic organic pollutants as well as antibiotics in water is urgent (In this study, the treatment of antibiotic pollutants including cefalexin (CF) and tetracycline (TC) was investigated by applying the advanced oxidation process based on Ni-doped TiO2 (Ni–TiO2 ). The characterizations technologies such as XRD, XPS, UV–vis, PL, and PC indicated that Ni doping would improve the photocatalytic performance of TiO2 . In the photodegradation experiments, the Ni–TiO2 possessed high photocatalytic degradation efficiencies with 93.6% for CF and 82.5% for TC. Besides, the removal rates of antibiotics after five cycles are higher than 75%, implying excellent stability of Ni–TiO2 photocatalyst. The result from the treatment of wastewater samples revealed that the Ni–TiO2 photocatalytic had good performance for removal of CF and TC at a high level of 88.6 and 80.2%, respectively. Highlights: Ni-doped TiO2 exhibits excellent photocatalytic performance for antibiotics degradation. Degradation rate of antibiotic by Ni–TiO2 was 40% higher than that of undoped TiO2 . Reusability of Ni–TiO2 was higher than 75% after 5 cycles. Ni–TiO2 could remove 88.6% of CF and 80.2% of TC 80.2% from wastewaters.